Improvement of PS-128 BIT Water Pump Production Process Using Six Sigma Method at PT Tirta Intimizu Nusantara - Nadia Mufida; Johson Saragih; Anik Nur Habyba (Jurnal Rekayasa Sistem & Industri, 2022)
Customer satisfaction is one of the company's benchmarks in maintaining product quality. One of the most demanded types of non-automatic pumps is the PS-128 BIT. Water pump problems that occur because the percentage of defects are still above the company's desired tolerance. The tolerance given by the company is 3%, but the percentage of defects received by the company is 5.93%. This percentage is obtained based on the average percentage of disability in five months (July – November 2021). Furthermore, the company needs to make improvements to the quality of the pump product. The purpose of the research is to minimize product defects to improve product quality and can meet customer satisfaction. The method used is six sigma. The results of the study identified that there are two types of defects that are dominant in pump products, namely leaking mseal and leaking o-ring. The calculation of value defect million per opportunity was obtained at 51,000 and converted into a sigma rate of 3.135 where this value can still be increased so that the level of defective products is reduced. Actions that can be taken to overcome leaky mseal include using a mseal part inspection checklist and leaky o-rings can be handled using tools such as air duster guns. This tool is used to help clean parts regularly to ensure that the part is clean and can be done to the next stage of the production process. This proposed improvement has been implemented with the final result of the sigma level increasing by 3.262.